2014
DOI: 10.1177/1076029614558113
|View full text |Cite
|
Sign up to set email alerts
|

Increased Epicardial Adipose Tissue Thickness is Associated With Angiographic Thrombus Burden in the Patients With Non-ST-Segment Elevation Myocardial Infarction

Abstract: We aimed to evaluate the relation among epicardial adipose tissue (EAT) thickness, angiographic presence of thrombus, and the no-reflow in the patients with non-ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention. The study population consisted of 229 patients. The EAT thickness and neutrophil to lymphocyte ratio (NLR) were significantly higher in the patients with coronary thrombus than in those without coronary thrombus (6.1 ± 1.1 vs 5.1 ± 1.3 mm, P < .001 and 3.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
1
7
0
2
Order By: Relevance
“…Due to these facts, EAT is thought to be related to the presence and the severity of CAD, coronary plaque morphology and plaque rupture, myocardial ischemia, and major adverse cardiac events (MACE) in patient with ACS. In a recent study, increased EAT thickness were independent predictors of coronary thrombus formation in patients with NSTEMI who underwent pPCI and also coronary thrombus formation was independently associated with no-reflow phenomenon 12 . In compatible with those studies, the present study has shown that EAT was an independent predictor of coronary thrombus burden in STEMI who underwent pPCI.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Due to these facts, EAT is thought to be related to the presence and the severity of CAD, coronary plaque morphology and plaque rupture, myocardial ischemia, and major adverse cardiac events (MACE) in patient with ACS. In a recent study, increased EAT thickness were independent predictors of coronary thrombus formation in patients with NSTEMI who underwent pPCI and also coronary thrombus formation was independently associated with no-reflow phenomenon 12 . In compatible with those studies, the present study has shown that EAT was an independent predictor of coronary thrombus burden in STEMI who underwent pPCI.…”
Section: Discussionmentioning
confidence: 91%
“…Epicardial adipose tissue is related with various genes associated with extracellular matrix remodeling, inflammation, infection, and thrombosis pathways 11 . Inflammatory cells play a major role both in plaque disruption through the matrix degrading metalloproteinases and in triggering thrombosis following plaque disruption through the tissue factor pathway 12 . During that process, tumor necrosis factor α (TNF-α), monocyte chemoattractant protein 1, interleukin 1β (IL-1β), interleukin 6 (IL-6), nerve growth factor, leptin, resistin, plasminogen activator inhibitor 1, and angiotensinogen especially WBC and many other pro-inflamatuar or anti-enflamatur cytokines have crucial roles within this cascade 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that age, diabetes mellitus, red cell distribution, intrinsic platelet reactivity, increased mean platelet volume at admission, increased epicardial adipose tissue thickness, bilirubin Levels, monocyte to HDL cholesterol ratio, SYNTAX score and absence of pre-infarction angina were independent predictors of TB in patients with STEMI. [14][15][16][17][18][19][20][21] In this cohort, we did not observe an association between the above mentioned predictors and intracoronary TB in these young adults with STEMI. Thus, the predictors for TB might thus be quite different in young STEMI patients as compared with general STEMI patient cohorts.…”
Section: Other Potential Independent Predictors Of Higher Tbmentioning
confidence: 85%
“…Previous studies showed that the extent of coronary TB in patients with STEMI was associated with age, diabetes mellitus, red cell distribution, intrinsic platelet reactivity, higher troponin and leukocyte concentrations, increased mean platelet volume, increased epicardial adipose tissue thickness, bilirubin levels, monocyte to high-density lipoprotein (HDL) cholesterol ratio and absence of pre-infarction angina. [14][15][16][17][18][19][20][21] It is to note that the study cohorts of above mentioned observations refereed mostly patient population aged >45-years old. Few studies focused on young STEMI patients (≤45 years), and data on determinants of coronary TB in young STEMI patients remain scarce.…”
mentioning
confidence: 99%
“…By autocrine and paracrine means, it generates various types of anti-/proin ammatory mediators and free fatty acids [8]. More recently, multiple clinical researches have shown that increased EAT deposition plays a pivotal role in the development and progression of ISR [9][10][11][12][13][14], no-re ow [15][16][17][18], infarct size [19,20] or MACE [4,5,13,14] for patients treated with PCI with inconsistent results.…”
Section: Introductionmentioning
confidence: 99%